Study of management policies of activities of scientific research and technological development for US corporation and companies - Dung, Bui Tien (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2017)
In the US, in addition to universities, national research institutes and specific research institutes of ministries, there is a system of laboratories of corporations and companies which carry out also fundamental researches, R&D and applied researches (making over 74% of the total volume of science-technology (S&T) activities). This study will provide a discussion on management policies of activities of scientific research and technological development applied for US corporations and companies including: introduction of types of US enterprises, orientation of entrepreneurial Government policies and management policies of S&T activities. These US experiences may open an approach for management policies of S&T activities for Vietnamese corporations and companies as well as for Vietnamese researchers and managers. Code: 13041601